Funcionários de escola: trajetórias e expectativas na construção de uma identidade profissional - Penteado, Sara Rimena de Avila (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation approached the construction of professional identity, the trajectory and the expectations of school employees, by means of a practical analysis of employees' professional activities at a private school in the metropolitan region of Porto Alegre. The theoretical framework that bases the study enabled it to trace a deeper analysis of the Profuncionário Program and the struggles, the advances and the challenges regarding professionalization of these school employees. By means of this research, it was possible: a) to investigate the way school employees perceive their professional performance in an educational institution; b) to understand these employees' perceptions/expectations concerning their professionalization process in school; c) to construct a diagnosis of their professional performance, and to design a preliminary proposal of continued education for them, considering the findings of this research. The methodological procedures used in this study were application of questionnaire and group interview. By means of the analyses, it was possible to show the necessity of consolidating the professional identity of school employees, as well as tracing, from the study of the Profuncionário Program, some themes that can guide the educational proposal designed for these professionals: School, Interpersonal Relations, Inclusion and Professionalism. The results of this study, in addition to bringing to light the importance of these employees for schools, yielded discoveries concerning daily expectations and yearnings of these professionals, and made possible to elaborate a proposal of continued education to be developed in the school.
Keywords: Funcionário de escola; Gestão educacional; Formação continuada; Programa Profuncionário; School employee; Educational management; Continued education; Profuncionário Program; ACCNPQ::Ciências Humanas::Educação